Structural variation in soft segment of waterborne polyurethane acrylate nanoemulsions. Issue 12 (1st December 2014) - Sultan, Misbah; Islam, Atif; Gull, Nafisa; Bhatti, Haq Nawaz; Safa, Yusra
ABSTRACT High solid content waterborne polyurethane acrylate (WPUA) nanoemulsions are prepared as textile finishes. Two structurally different soft segments, that is, polyether and polyester are used with isophorone diisocyanate, 2‐hydroxyethyl methacrylate, and butyl acrylate. Structural variations are investigated in features of nanoemulsions and their coatings. Physical properties of nanoemulsions, such as average particle size, stability, solid content, and viscosity, are investigated. Nanoemulsions with high solid content, that is, 40–47% are produced without any internal emulsifier. Average nanoparticle size, that is, <100 nm is confirmed by dynamic light scattering and atomic force microscopy (AFM). Fourier transform infrared spectroscopy proved synthesis of proposed WPUA products. Synergistic effect of polyurethane and acrylate is observed in chemical and water resistance of WPUA. Differential scanning calorimetry (DSC) and thermogravimetric analysis indicate stable uniformly cross‐linked network of WPUA. Application of nanoemulsions on 100% cotton fabric shows a significant improvement in tear strength, which is more pronounced for polyester‐based WPUA. Scanning electron microscope images of treated fabric samples show good adhesion of nanoemulsions on cotton surface. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41706.